'Minha casa, minha vida' e os efeitos socioespaciais no município de Vila Velha/ES - Krohling, Wildes (2016)
The latest government action in Brazil to try to solve the problems faced in the housing issue is the “Minha Casa Minha Vida” Program (PMCMV), launched in 2009. Designed in partnership between the federal government and some construction companies, it soo